061 The long-term effects of anterior temporal lobe resection on memory encoding: A longitudinal fMRI study. Issue 9 (12th August 2022) - Fleury, Marine; Buck, Sarah; Thompson, Pamela; Duncan, John; Sidhu, Meneka
Abstract : Episodic memory functions are impaired in up to 40% of patients with temporal lobe epilepsy (TLE) following anterior temporal lobe resection (ATLR). Little is known of plasticity effects beyond one year postoperatively. We describe the dynamic plasticity of memory encoding networks long-term after ATLR. Sixteen patients with TLE (8 left-sided) and six controls performed a memory-encoding fMRI paradigm of faces and words across equivalent time-points (pre-surgery, 4, 12 months, and 7–10 years post-surgery). Flexible factorial designs probed the changes in fMRI activations in patients between 12 months and long-term postoperatively, relative to longitudinal changes in controls. Clinical memory scores (list- and design-learning) were correlated with changes in activations. From 1 to 10 years postoperatively, prefrontal cortex (PFC) activations were increased ipsilaterally for word encoding after left ATLR and bilaterally for face encoding after left and right ATLR. After left ATLR, improvement in visual memory correlated with increased contralateral amygdala, insula, and PFC acti- vations. After right ATLR, right fusiform gyrus and temporo-parietal activations positively correlated with visual memory. Better verbal memory correlated with increased right fusiform gyrus and PFC activations. Years after left and right ATLR, there is continued contralateral and ipsilateral plasticity which is supportive of memory functions.